Pengaruh Tayangan 2gether: The Series Terhadap Sikap Toleransi Perempuan Mengenai Homoseksual - Fernanda Khairunnisa Venturini; Fardiah Oktariani Lubis; Oky Oxcygentri (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Boys love as a global phenomenon has getting attention for many people since it stories about homosexual relationship. It gains positive respond for many people. Moreover, the appearance of one of famous series about homosexual relationship from Thailand, 2gether: The Series, has influence the success of the Boys Love so that it become popular in entire of world especially in Indonesia, the country which has a lot of fans for Boys Love series.The purpose of this study is to determine the effect of 2gether: The Series based on three dimensions of applied theory used, namely Uses and Gratification theory covering frequency, duration and attention to women's tolerance attitudes about homosexual. Respondents for this study are from followers of the twitter account @thaiifess, totaling 100 people, female and people who are having watched 2gether: The Series. This study uses a quantitative approach with a survey method. Data analysis to be used in this reserch is multiple linear regression analysis technique. The research shows that there is an effect of simultaneous 2gether: The Series on women's tolerance attitudes about homosexuals based on a coefficient of determination of 16.4%. The dimensions of the variable X (frequency, duration and attention) indicate that the highest contribution, attention is 0.16 and the lowest is the frequency of -0.003.